FORMATION OF THE CONCEPTUAL PROVISIONS OF THE STATE POLICY OF IMPROVING THE INSTITUTIONAL PROVISION OF INNOVATIVE AND TECHNOLOGICAL COMPETITIVENESS AND ECONOMIC SECURITY OF THE STATE (Development Service Industry Management, 2025)
The research focuses on issues of public policy of regulation of innovative and technological activity, development and provision of technological competitiveness and economic security of the state. The purpose of the article is to generalize and further develop the theoretical and methodological foundations of the state policy for the development of institutional support for innovative technological competitiveness and economic security of the state. It has been proven that technological competitiveness has its own principles that need to be taken into account when forming the methodology of its study. The fundamental principles in this area are revealed - comprehensive assessment, competitiveness and floating targeting, extensive-intensive balancing, identification of the basis of comparison, comparability of competitive positions, realization of opportunities, dynamism of goals and results, combination of structuring and unity of the system, rational distribution of costs and results, orientation to realization of potential. The classification features of the conceptual provisions of the state policy in the field of institutional support of innovative and technological competitiveness and guaranteeing the economic security of the state are determined according to: integral indices, evaluation methods, objects of implementation of the results of innovative and technological development, forms of their presentation, variables, that are analyzed, methods of determining weighting factors, levels of spatial penetration, basic aspects of ensuring international competitiveness, approaches to determining boundaries and thresholds. It has been proven that the successful implementation of state policy in the field of formation and development of a high-quality institutional environment for the technological competitiveness of the national economy is based on the results of generalization with the subsequent implementation of the most optimal for the country models, strategies and tactics, regulatory mechanisms.
Keywords: national economy; economic security; innovation and technological competitiveness; strengthening; state policy; institutional support